Undergraduate Nursing Student’s Self-Efficacy Towards Palliative Care: A Rapid Narrative Review - Nurul Sopia; Hana Rizmadewi Agustina; Hesti Platini (Indonesian Journal of Global Health Research, 2024)
The increasing number of patients with life-threatening diseases will affect the high need for palliative care in health services. Self-efficacy towards palliative care among undergraduate students is vital for ensuring they have adequate readiness and ability to provide high-quality care. Objective : This review aims to identify the level of self-efficacy towards palliative care among undergraduate nursing students. Method : The method used in this literature review is a rapid narrative review compiled using PRISMA 2020 guidelines. The databases used were PubMed, Medline, Scopus and ScienceDirect. Articles used are research articles with published from 2020-2024. The criteria in this study were organized based on the PCC framework criteria. The main keywords were not limited to “undergraduate nursing student*”, “self-efficacy”, and “palliative care”. Results : Nine out of 167 studies were included. The findings discussed the level of self-efficacy and factors that influence self-efficacy towards palliative care in clinical learning among undergraduate nursing students. Conclusions : Low self-efficacy indicates undergraduate nursing students' unpreparedness to provide palliative care. Nursing students need self-efficacy towards palliative care to ensure adequate readiness and ability to provide high-quality palliative care. This review is essential to improve the quality of palliative care education and increase self-efficacy in undergraduate nursing students.